The Effectiveness of Training Mindfulness, Self-Compassion, and Self-Regulation on Physical Activity Enjoyment among Obese and Overweight Students - Reza Nazeri; Hossein Lotf Abadi; Hossein Pourshahryar (Shiraz University of Medical Sciences, 2018)
Background: Today, lifestyle-associated health problems are increasing, while healthy behaviors could reduce their consequences, e.g. mortality. The physical activity enjoyment (PAE) is one of the most important factors which might lead to enhanced physical activity, as a protective factor of chronic diseases and mental disorders. The main purpose of this research was to study the effectiveness of educating mindfulness, self-compassion and self-regulation on the PAE of obese and overweighed students. Methods: This is a semi-experimental pre-post study on the effects of educational interventions on the PAE among the high-school students. After informing all participants about the goals of the research, through a list generated based on block randomization methods with size 4 in each block, they were divided randomly into 4 training groups (17 students per group). To assess the PAE, the valid and reliable version of 18-items questionnaire made by Kendzerski and Decarlo (1991) was employed. Results: All participants were in grade 9 aging 14-16 years. Their BMI had a mean of 32.10±2.35 (ranged 26.22 to 37.28). All of the experimental groups had significantly higher levels of PAE than the control group. Conclusion: The educational methods had a significant effect on increasing PAE. Mindfulness, self-compassion, and self-regulation might be used as educational methods to increase the PAE.